Formation of Mass Media Law in the Post-Soviet Russia: Constitutional Foundations and Stages - PIRBUDAGOVA, Diana Shamilyevna; OMAROVA, Anzhelika Mikhailovna (Journal of Advanced Research in Law and Economics; Vol 11 No 2 (2020): JARLE Volume XI Issue 2(48) Spring 2020, 2020)
Today, countries are developing new forms of interaction between state and mass media and expanding their regulatory frameworks. In several states, specific integrated institutes and legal sectors have been formed that regulate the legal status of mass media. Since the early 1990s, the Russian Federation has been working on special rules governing the constitutional status of mass media. During this period, a comprehensive media institute formed in the framework of information law, which later transformed into mass media law. The evolution of this institute is of particular scientific interest, as Russia did not have any law on mass media until the end of the 20 th century.